DEMOCRATIZATION OF EXECUTIVE POWER AND MANAGEMENT – THE MOST IMPORTANT PRIORITY OF FURTHER DEVELOPMENT OF DEMOCRATIC REFORMING IN THE COUNTRY - Yuldash Djumayev (European Scientific Journal, ESJ, 2013)
In this article, the author analyses the democratization of executive power and management as the most important priority of further developing of democratic reforms in the country. It is known, that main support of democratic image of government, is provided by division of power. An article represents examples from history concerning division of power, principles of introduction of checks and balances system in public administration. Moreover, opinions of the article's author are proved by opinions on the matter of such great thinkers of history, as Pláton, Aristotle, Polibiy, S.L. Montesquieu, D. Lilbern, J. Lock and others. Besides, the thoughts of President of the Republic of Uzbekistan I.A. Karimov, which are actual even nowadays, are brought in the article. The statements, which have been put forward in article, are actively realized in the country. Additionally, the Concept of further developing the democratic reforms and formation of civil society in the country, which is offered by the President of the Republic of Uzbekistan, forms the base of the actual state and public construction in the Republic of Uzbekistan. Offers in this Concept, for example, amendments and supplements in the Changes and additions are brought in the Constitution of the Republic of Uzbekistan with a view at further deepening of democratic reforms and formation of civil society, democratization of governmental authorities and management, ensuring more balanced distribution of powers between three subjects of the government. In the majority of developed countries, the institute of a vote of no confidence in which the disapproval of governmental activities is expressed, acts as a key instrument of influence of parliament on the government. Same a way adheres also to the Republic of Uzbekistan. In addition, it is remarkable, that according to the offer of fractions, the reports from heads of the ministries and departments are included in the Program within parliamentary hearings on such questions.